Критериумот на вистината во стоичката филозофија - Наумоска, Јасмина (Živa Antika / Antiquité Vivante, 2010)
The concept of the criterion of truth takes leading role in the Hellenistic epistemological reflections. The Stoic’s position concerning this question is extremely relevant for the ancient philosophy since, along with Epicurus’ position, brings the “epistemological turn” in philosophy. This article seeks to present the Stoic theory of the criterion of truth and the characteristic answers that it offers, namely, to analyze the Stoic use of the terms “true” and “truth”, the meaning of “λεκτόν” as a truth value carrier, the specific use of the term “criterion” distinct from the Epicurean usage, and to argue about the concept of prolepsis as specific criteria. Although the theory of the criterion has its own value in the Stoic epistemology, the theory of knowledge gets its own application for the first time in the philosophical inquiry. The logic now has therapeutic function and laying foundation of unequivocal criterion of truth becomes “remedium animae”.